Congenital heart disease in the newborn requiring early intervention - Sin Weon Yun (Korean Pediatric Society, 2011)
Although antenatal diagnostic technique has considerably improved, precise detection and proper management of the neonate with congenital heart disease (CHD) is always a great concern to pediatricians. Congenital cardiac malformations vary from benign to serious conditions such as complete transposition of the great arteries (TGA), critical pulmonary and aortic valvular stenosis/atresia, hypoplastic left heart syndrome (HLHS), obstructed total anomalous pulmonary venous return (TAPVR), which the baby needs immediate diagnosis and management for survival. Unfortunately, these life threatening heart diseases may not have obvious evidence early after birth, most of the clinical and physical findings are nonspecific and vague, which makes the diagnosis difficult. High index of suspicion and astute acumen are essential to decision making. When patent ductus arteriosus (PDA) is opened widely, many serious malformations may not be noticed easily in the early life, but would progress as severe acidosis/shock/cyanosis or even death as PDA constricts after few hours to days. Ductus dependent congenital cardiac lesions can be divided into the ductus dependent systemic or pulmonary disease, but physiologically quite different from each other and treatment strategy has to be tailored to the clinical status and cardiac malformations. Inevitably early presentation is often regarded as a medical emergency. Differential diagnosis with inborn error metabolic disorders, neonatal sepsis, persistent pulmonary hypertension of the newborn (PPHN) and other pulmonary conditions are necessary. Urgent identification of the newborn at such high risk requires timely referral to a pediatric cardiologist, and timely intervention is the key in reducing mortality and morbidity. This following review deals with the clinical presentations, investigative modalities and approach to management of congenital cardiac malformations presenting in the early life.